Rosanti,Fatma PEMANFAATAN APLIKASI KEJAR.ID SEBAGAI LEARNING MANAGEMENT SYSTEM (LMS) DALAM PELAJARAN INFORMATIKA DI SMK ISLAM 2 WLINGI: Abstrak,Pendahuluan,Metode,hasil dan pembahasan,kesimpulan - Rosanti, Fatma (Journal of Practice Learning and Educational Development, 2025)
This study aims to evaluate the use of the Kejar.id application as a Learning Management System (LMS) in Informatics learning at SMK Islam 2 Wlingi. In the digital era, technology integration in learning is a necessity, especially in teaching subjects related to technology itself. The Kejar.id application is used as a means to support an interactive, efficient, and flexible learning process. The method used in this study is the Classroom Action Research (CAR) model of Kemmis and McTaggart with two cycles. The subjects of the study were grade X students of the Software Engineering expertise program. The instruments used included teacher and student observation sheets, as well as Lesson Implementation Plans (RPP). The results of the study showed an increase in learning effectiveness from cycle I to cycle II, both in terms of planning, implementation, and observation. The use of Kejar.id makes it easier for teachers to manage materials and assignments and increases student engagement in learning. The conclusion of this study is that Kejar.id is effective for use as an LMS in Informatics learning and can be used as an alternative digital-based learning solution in SMK.